Support vector machines for biomedical applications - Chaw, Su Khine. (2008)
Support Vector Machine Classification has been carried out on Cancer and Heart problems derived from Proben 1, an artificial standard benchmarking problem. The results data between SVM and BP will be compared to detect cancer and heart problem and used to contribute to the application of support vector machines in the biomedical aspect.